2003
DOI: 10.7773/cm.v29i42.188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the seaweed Macrocystis pyrifera and a formulated diet on growth and fatty acid composition in the green abalone, Haliotis fulgens, under commercial culture conditions

Abstract: The effect of a formulated diet (FD), a seaweed diet (SW), and a mixture of both (FD + SW) on growth, survival rate, and fatty acid content in the tissue of juvenile Haliotis fulgens abalone grown under commercial culture conditions, was analyzed over a 329-day period. Survival and growth rate in terms of length and weight were different with each of the diets evaluated, being significantly higher (P < 0.05) with the mixed diet (FD + SW), followed by SW and FD. Since feed intake was not evaluated in this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…A study on the South African abalone Haliotis midae has also shown that combination diets consisting of a fresh macroalgae fed in conjunction with a formulated feed outperform the formulated feed fed alone (Dlaza et al, 2008). Durazo-Beltrán et al (2003) reported significantly improved growth rates for Haliotis fulgens on a combination diet (M. pyrifera and 31% protein formulated pellet) compared to either of its components fed individually. Dang et al (2011) showed similar growth for Haliotis laevigata on formulated and a combination diet, both of which outperformed monospecific algal diets.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A study on the South African abalone Haliotis midae has also shown that combination diets consisting of a fresh macroalgae fed in conjunction with a formulated feed outperform the formulated feed fed alone (Dlaza et al, 2008). Durazo-Beltrán et al (2003) reported significantly improved growth rates for Haliotis fulgens on a combination diet (M. pyrifera and 31% protein formulated pellet) compared to either of its components fed individually. Dang et al (2011) showed similar growth for Haliotis laevigata on formulated and a combination diet, both of which outperformed monospecific algal diets.…”
Section: Discussionmentioning
confidence: 95%
“…As Chilean farmers were reluctant to convert to pelleted diets, the option of combination diets (i.e., macroalgae and formulated feed fed together) thus provided a pathway for abalone farmers to explore the use of formulated feeds without abandoning macroalgal dietary options entirely. Combination diets allow for an extended weaning period to facilitate dietary switch and there is a growing body of literature to suggest that combination diets provide superior production outcomes when compared to single diets, either macroalgal or formulated (Dlaza et al, 2008;Durazo-Beltrán et al, 2003;Naidoo et al, 2006). The effect of diet on the growth of abalone in commercial culture must however always be balanced against its effect on the quality and yield of the final product.…”
Section: Introductionmentioning
confidence: 97%
“…2003; Nava‐Guerrero et al. 2004) and establishing the effect of formulated diets on the biochemical composition of tissues of green abalone (Durazo‐Beltrán et al. 2003a,b, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…An abundant literature describes the nutritional value of marine plants consumed by abalone, and artificial diets have been extensively tested over the past two decades, chiefly to support refinements in abalone aquaculture (Uki & Watanabe 1992;Leighton 2000). Several studies on nutrition for green abalone in Mexico have been conducted, largely focusing on evaluating different conventional and unconventional protein sources for artificial diets (Viana-Castrillo´n 2002;Go´mez et al 2003;Nava-Guerrero et al 2004) and establishing the effect of formulated diets on the biochemical composition of tissues of green abalone (Durazo-Beltra´n et al 2003a,b, 2004.…”
mentioning
confidence: 99%
“…No significant differences in feed intake were observed among treatments, including the reference (Rd) treatment, even when the P/E ratio was 35 compared to 93-105 found in the formulated diets. It is known that for abalone, as well as for previos se ha demostrado que H. fulgens es capaz de sintetizar HUFAs para compensar los efectos de las bajas temperaturas de las aguas donde habita (Durazo-Beltrán et al 2003b). Aquí, las distintas dietas utilizadas, con perfiles de ácidos grasos claramente diferentes particularmente en HUFA n3, no fueron capaces de inducir diferencias en el perfil correspondiente del tejido muscular.…”
Section: Initialmentioning
confidence: 99%